Report proposed of new interior design scheme of Audi showroom at Lot 132, Section 41, Jalan Sultan Ismail, 50250 Kuala Lumpur, for Euromobil Sdn. Bhd. / Nadzmi Samsudin - Samsudin, Nadzmi (Faculty of Architecture, Planning and Surveying, 2009)
Proposing a new interior design scheme for Audi showroom in Kuala Lumpur is an idea given by my client itself, who wanted to open up a new branch showroom in the heart of the city of Kuala Lumpur. This is part of their plan on expanding their sells to and to make the car brand becoming the top premium brand car maker in Malaysia by the year 2010. They wanted the new showroom to follow the same standard company design that the Audi AG has come out on the year 2008. They wanted the new showroom to up hold the identity of Audi and the image that they represent. The client felt it is time to redesign all Audi showrooms in Malaysia to its current image so that the showroom will reflect the recent development batch of new design models that come out. They want the new showroom to make an impact to Malaysian and the brand will be the coming trend of exotic and exclusive cars in the country as it did to Mercedes Benz and BMW.